Maximizing reader response in an interactive classroom - Diaz de Rivera, Lina B. (Education Quarterly, 1992)
The use of literature as authentic text in interactive reading classrooms is recommended with special focus on folklore materials.The features of reader-response approaches are likewise discussed as well as examples of student-centered activities.